EFFECT OF RUANGANJIEDU DECOCTION INHIBIT EXPERIMENTAL HEPATIC FIBROSIS OF RATS. - Liu, Sheng; Wang, Xiao-min; Yang, Guo-wang (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: RuanGanJieDu (RGJD) is a traditional Chinese medicine comprising nine Chinese medicinal herbs. The clinical use of RGJD by us was found that it has a good control effect on hepatic fibrosis (HF) patient. In order to further investigate the Anti-fibrosis mechanism of RGJD, hence this experiment has been carried out. Methods: After treatment, the general conditions of rats in each group were observed. The liver tissues morphology and HF phases were observed under light microscope. The weights of livers and spleens were recorded; the indices of liver and spleen were calculated. The α-SMA and E-cadherin of the liver tissues were determined by Immunohistochemistry, and the contents of ALT、AST and PCIII+PCIV+HA+LN in rat serum were detected by ELISA. Results: After treatment, the rats in model group presented with abdominal distention and rough hair, lethargy and mental sluggishness, slow movement and irritability; Most rats in RGJD group and colchicine(Col) group were in good spirits and no obvious abnormal motion state. The RGJD had shown significant effects in improving the liver tissue morphology. The HF phases of RGJD group and Col group mainly distributed in the S1-S2 phases, were finer than the model group in the S3 phase (P<0.05). The wet weights and indices of livers and spleens in RGJD group were lower than the control groups (P<0.05). Moreover, the expressions of E-cadherin, α-SMA and the serum levels of AST, ALT and PCIII+PCIV in RGJD group were obviously decreased than the control groups except HA and LN(P<0.05). Conclusion: RGJD can improve the liver tissue morphology and reduce serum biochemical and collagen indices of HF, which proved a better curative effect of Chinese medicine than Col on HF and improving liver function.